Module Design of Earth and Space Science Practicum Based on Generic Ability of Science V Semester Students of Physics Education Program - Abdul Rajab; Ashar, Hasbullahair; Suhardiman, Suhardiman; Jamilah, Jamilah (Al-Khazini, 2023)
This research is a research and development which aims: (1) To develop and determine the validity level of the Science practicum module Earth and Space based on the generic science abilities of fifth semester students of the physics education study program. The development of the Earth and Space Science practicum module is carried out using the ADDIE development model. The stages in this study are limited only to the Development stage. Data collection techniques were obtained from 2 validators who were lecturers in the Physics Education Study Program, Alauddin State Islamic University Makassar. The data analysis technique used in the study only uses validity analysis. The results showed that: the Earth and Space Science practicum module based on generic science abilities that was developed met the valid criteria with an average value for all aspects of V = 0.86. Overall the value is categorized as "Very Valid" (˃0.8), so that the earth and space science practicum module based on generic science capabilities is declared to meet the validity criteria and is suitable for use.